PENGARUH MODAL, JAM KERJA, LAMA USAHA, DAN E-COMMERCE TERHADAP PENDAPATAN USAHA BABI GULING DI KOTA DENPASAR - Saputra, I Wayan Algi; Suasih, Ni Nyoman Reni (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 11 (2023): Vol.12.No.11. NOVEMBER 2023, 2023)
The study investigates the impact of capital, working hours, business duration, and e-commerce on the suckling pig (Babi Guling) business in Denpasar City. Babi Guling, a traditional Balinese dish, has transitioned from being solely associated with religious events to becoming a culinary attraction for tourists, potentially boosting tourism in Bali. The study categorizes Babi Guling as a Micro, Small, and Medium-sized Enterprise (MSME) under Government Regulation no. 7 of 2021. The research employs primary data and adopts Roscoe's theory due to an unknown population size. Accidental sampling is used to select participants who meet specific criteria within Denpasar City's four sub-districts. Data analysis utilizes multiple linear regression. Findings reveal that capital, working hours, business duration, and e-commerce collectively influence the income of Babi Guling ventures in Denpasar City. Individually, capital, working hours, and business duration significantly impact income. Moreover, Babi Guling businesses in Denpasar City that incorporate e-commerce generate higher average earnings compared to those not utilizing e-commerce. keyword : Capital, Working Hours, Business Duration, and e-commerce